2008
DOI: 10.1007/s12275-008-0235-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of methyl gallate and gallic acid on oral bacteria

Abstract: This study examined the ability of methyl gallate (MG) and gallic acid (GA), the main compounds of gallo-tannins in Galla Rhois, to inhibit the proliferation of oral bacterial and the in vitro formation of Streptococcus mutans biofilms. The antimicrobial activities of these compounds were evaluated in vitro using the broth microdilution method and a beaker-wire test. Both MG and GA had inhibitory effects on the growth of cariogenic (MIC<8 mg/ml) and periodontopathic bacteria (MIC=1 mg/ml). Moreover, these comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
148
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(161 citation statements)
references
References 25 publications
10
148
0
3
Order By: Relevance
“…It is well known that the polyphenols show goof antibacterial effect [31]. High concentrations of phenolic compounds are toxic both for the plants and the microorganisms [32,33]. …”
Section: Hplc Resultsmentioning
confidence: 99%
“…It is well known that the polyphenols show goof antibacterial effect [31]. High concentrations of phenolic compounds are toxic both for the plants and the microorganisms [32,33]. …”
Section: Hplc Resultsmentioning
confidence: 99%
“…AlZahrani (2012) reported MIC values in the range of 3.5-12.5 µg/ml against methicillin-resistant S. aureus. Kang et al (2008) investigated the susceptibility of Streptococcus mutans, Lactobacillus casei, and Lactobacillus acidophilus to gallic acid and found an MIC value of 8000 µg/ml using the microdilution method. Furthermore, Nohynek et al (2006) reported good antibacterial activities of gallic acid against Helicobacter pylori, Bacillus cereus, and Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid (3,4,5-trihydroxybenzoic acid, GA), a naturally occurring plant phenol, is abundant in natural plants (15)(16)(17)(18)(19) and it has been reported to have anti-bacterial (20), anti-viral (21), anti-inflammatory (16), antioxidant (22) and antitumor functions in many human cancer cell lines (21)(22)(23). Although GA has been shown to inhibit the growth of prostate cancer cells, there is no available information addressing GA-inhibited migration and invasion of prostate cancer cells in vitro.…”
Section: Introductionmentioning
confidence: 99%